Facilitating Out-of-Home Caregiving Through Health Information Technology: Survey of Informal Caregivers' Current Practices, Interests, and Perceived Barriers - Zulman, Donna M; Piette, John D; Jenchura, Emily C; Asch, Steven M; Rosland, Ann-Marie (JMIR Publications, 2013)
BackgroundMany patients with chronic conditions are supported by out-of-home informal caregivers-family members, friends, and other individuals who provide care and support without pay-who, if armed with effective consumer health information technology, could inexpensively facilitate their care. ObjectiveWe sought to understand caregivers' use of, interest in, and perceived barriers to health information technology for out-of-home caregiving. MethodsWe conducted 2 sequential Web-based surveys with a national sample of individuals who provide out-of-home caregiving to an adult family member or friend with a chronic illness. We queried respondents about their use of health information technology for out-of-home caregiving and used multivariable regression to investigate caregiver and care-recipient characteristics associated with caregivers' technology use for caregiving. ResultsAmong 316 out-of-home caregiver respondents, 34.5% (109/316) reported using health information technology for caregiving activities. The likelihood of a caregiver using technology increased significantly with intensity of caregiving (as measured by number of out-of-home caregiving activities). Compared with very low intensity caregivers, the adjusted odds ratio (OR) of technology use was 1.88 (95% CI 1.01-3.50) for low intensity caregivers, 2.39 (95% CI 1.11-5.15) for moderate intensity caregivers, and 3.70 (95% CI 1.62-8.45) for high intensity caregivers. Over 70% (149/207) of technology nonusers reported interest in using technology in the future to support caregiving. The most commonly cited barriers to technology use for caregiving were health system privacy rules that restrict access to care-recipients' health information and lack of familiarity with programs or websites that facilitate out-of-home caregiving. ConclusionsHealth information technology use for out-of-home caregiving is common, especially among individuals who provide more intense caregiving. Health care systems can address the mismatch between caregivers' interest in and use of technology by modifying privacy policies that impede information exchange.